Absolutism, Relativism, and Universalism in Personality Traits Across Cultures: The Case of the Big Five. (August 2022) - Thalmayer, Amber Gayle; Saucier, Gerard; Rotzinger, Julia S.
Personality is a broad concept used to organize the myriad ways that people differ psychologically from one another. There is evidence that such differences have been important to humans everywhere, in that personality-relevant terms appear in all known languages. Empirical attempts to identify the most useful individual differences and their structure have emphasized cross-cultural evidence, but rigid adherence to a Big Five model has sometimes meant ignoring heterogenous results. We start with a framework for more precisely defining the universality versus cultural-specificity of personality concepts and models in order to better assess cross-cultural evidence. As this 50th anniversary of the IACCP is also the 50th anniversary of the first large lexical study of personality and more or less of the Big Five model, we take the opportunity to explore both how personality has been studied across contexts using the lexical method, and in 100 articles on personality topics (most using questionnaires) that were identified in the pages of JCCP . Personality articles in JCCP, classified into three types based on their balance of emic and etic components, illustrate larger trends in personality psychology. With the benefit of hindsight, we reflect on what each type has to offer going forward, and we encourage cross-cultural personality psychologists to go beyond imposed etic studies that seek primarily to confirm Western models in other contexts. The kinds of insights that more integrative emic and etic approaches can bring to the study of psychology across cultures are highlighted, and a future research agenda is provided.